1990
DOI: 10.1007/bf00000046
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations of pancreatic microvasculature in cerulein-induced pancreatitis in the rat

Abstract: Pancreatic microvasculature in cerulein-induced pancreatitis was studied at the electron and light microscopic level. Using a modified model of in situ india ink perfusion, focally a marked reduction of the number of india-ink-filled microvessels was found. The numerical density (NA) of filled microvessels was reduced by 66.7% in pancreatitis. The morphological correlate for this extreme numeric reduction might be a collapse of the lumen of pancreatic microvessels. In the presence of cerulein pancreatitis 42% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…It has been reported that blood flow within the pancreas is already drastically reduced very early during acute pancreatitis (Gress et al 1990;McEntee and Kelly 1991) so that adverse effects on the physiological functions of the gland might be expected. Prevention of the oedema by icatibant could thus be expected to be beneficial also in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that blood flow within the pancreas is already drastically reduced very early during acute pancreatitis (Gress et al 1990;McEntee and Kelly 1991) so that adverse effects on the physiological functions of the gland might be expected. Prevention of the oedema by icatibant could thus be expected to be beneficial also in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Enclosure of intracellular organelles within autophagic vacuoles with subsequent lysosomal degradation appears to contribute to the destruction of the acinar cells in this model of acute pancreatitis 12,13 . During caerulein-induced pancreatitis there is a collapse in the pancreatic capillaries and surface blebbing, formation of cytoplasmatic vacuoles, edema, and swollen mitochondria in the 14,15,16 . These structural alterations were present early in the experimental edematous pancreatitis 14 .…”
Section: Resultsmentioning
confidence: 99%
“…During caerulein-induced pancreatitis there is a collapse in the pancreatic capillaries and surface blebbing, formation of cytoplasmatic vacuoles, edema, and swollen mitochondria in the 14,15,16 . These structural alterations were present early in the experimental edematous pancreatitis 14 . Overall, experimental 17 and clinical 5 studies have found that during acute pancreatitis there is a decrease in the blood flow to the pancreas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations